Comparison of different quasi-static loading conditions of additively manufactured composite hexagonal and auxetic cellular structures. (15th April 2023) - Zhou, Jin; Liu, Haibao; Dear, John P.; Falzon, Brian G.; Kazancı, Zafer
Highlights: Hexagonal, re-entrant and double arrowhead structures compared under different quasi-static loading conditions. Computational modelling has considered cell wall thickness for a better agreement with the experimental deformation. Superior specific energy absorption and compressive strength obtained from double arrowhead (auxetic) composite cellular lattices. Abstract: Auxetic cellular structures have the potential to revolutionise sandwich panel cores due to their potential superior energy absorption capability. Because of their negative Poisson's ratio, auxetics behave counterintuitively and contract orthogonally under an applied compressive force, resulting in a densification of material in the vicinity of the applied load. This study investigates three cellular structures and compares their compressive energy absorbing characteristics under in-plane and axial loading conditions. Three unit cell topologies are considered; a conventional hexagonal, re-entrant and double arrowhead auxetic structures. The samples were additively manufactured using two different materials, a conventional Nylon and a carbon fibre reinforced composite alternative (Onyx). Finite element simulations are experimentally validated under out of and in-plane loading conditions and the double arrowhead (auxetic) structure is shown to exhibit comparatively superior energy absorption. For the carbon fibre reinforced material, Onyx, the specific energy absorbed by the double arrowhead geometry was 125% and 244% greater than the hexagonal (non-auxetic) and re-entrant (auxetic) structures respectively. Graphical Abstract: Image, graphical abstract